2007
DOI: 10.1124/mol.107.039255
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Roles of Serines 5.43(239) and 5.46(242) for Binding and Potency of Agonist Ligands at the Human Serotonin 5-HT2A Receptor

Abstract: We assessed the relative importance of two serine residues located near the top of transmembrane helix 5 of the human 5-HT 2A receptor, comparing the wild type with S5.43(239)A or S5.46(242)A mutations. Using the ergoline lysergic acid diethylamide (LSD), and a series of substituted tryptamine and phenethylamine 5-HT 2A receptor agonists, we found that Ser5.43(239) is more critical for agonist binding and function than Ser5.46(242). Ser5.43(239) seems to engage oxygen substituents at either the 4-or 5-position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
75
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 36 publications
11
75
1
Order By: Relevance
“…Affinity and Function of (1) 3 H]ketanserin at m5-HT2A A5.46S and h5-HT2A S5.46A receptors were 1.2 6 0.3 and 1.6 6 0.4 nM, respectively, closely matching many reported literature values (Almaula et al, 1996a;Braden and Nichols, 2007) and not statistically different from 5-HT2A WT receptors (P . 0.05).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Affinity and Function of (1) 3 H]ketanserin at m5-HT2A A5.46S and h5-HT2A S5.46A receptors were 1.2 6 0.3 and 1.6 6 0.4 nM, respectively, closely matching many reported literature values (Almaula et al, 1996a;Braden and Nichols, 2007) and not statistically different from 5-HT2A WT receptors (P . 0.05).…”
Section: Resultssupporting
confidence: 77%
“…Thus, the interaction of the (1)-6-OH-7-Cl-PAT 6-OH moiety with S5.46 was crucial for its binding, whereas this amino acid hardly impacted binding of (2)-6-OH-7-Cl-PAT. This observation is unusual compared with most other 5-HT2A-targeting compounds reported (Almaula et al, 1996a;Braden and Nichols, 2007;Shan et al, 2012), including DOI. For example, of more than 20 compounds tested, only the ergot derivatives, e.g., ergonovine, showed major losses in affinity at the human S5.46A 5-HT2A receptor (Almaula et al, 1996a;Braden and Nichols, 2007).…”
Section: Discussioncontrasting
confidence: 40%
“…Although some of the compounds studied by Martí-Solano et al (2015) did have a high bias for PI signaling over AA release, the basis for their structural conclusions must be considered suspect because of significant flaws in their molecular modeling. For example, Braden and Nichols (2007) showed that TM5 serine 239 (5.43) in the 5-HT 2A receptor was critical for high affinity and potency of 4-or 5-oxygenated tryptamines, potentially serving as a hydrogen bond donor to the ligand, but Martí-Solano et al (2015) essentially ignore its role in their molecular dynamics simulations. In addition, they (incorrectly) state that "S5.43 is able to establish indirect interactions with different serotonergic agonists," citing Psychedelics Braden and Nichols (2007).…”
Section: Nicholsmentioning
confidence: 99%
“…Although indoles engage Ser242 within the human 5-HT 2A receptor, the dimethoxy-substituted phenethylamines do not. 80 The bicyclic indole nucleus of serotonin also is larger than the phenyl ring of the phenethylamines, and it seems possible that the hydrophobic 4-substituent of the phenethylamines acts as a sort of wedge or spacer to fill more fully the binding cavity that has evolved to accommodate the relatively larger indole nucleus of serotonin.…”
Section: Ring Substituentsmentioning
confidence: 99%
“…Construction of a homology model of the 5-HT 2A receptor from this in silico-activated rhodopsin template, and virtual docking with various 5-HT 2A agonist ligands, allowed the formulation of a number of hypothesis about the functional topography of the ligand binding site, which were subsequently validated by site-directed mutagenesis and ligand testing. 80,106 In addition, virtual docking studies allowed the design of new agonist ligands as well as the prediction of their more active enantiomers. 104,105 More recently, Isberg et al 79 have developed an in silico-activated model of the 5-HT 2A receptor starting with the published crystal structure of the β-2-adrenergic receptor.…”
Section: Receptor Modelsmentioning
confidence: 99%